2011
DOI: 10.1007/s10551-011-1171-8
|View full text |Cite
|
Sign up to set email alerts
|

All in the Mind? Ethical Identity and the Allure of Corporate Responsibility

Abstract: This paper develops a critique of the concept of 'ethical identity' as this has been used recently to distinguish between 'cynical' and 'authentic' forms of corporate responsibility. Taking as our starting point Levinas' demanding view of responsibility as 'following the assignation of responsibility for my neighbour', we use a case study of a packaging company-PackCo-to argue that a concern with being seen and/or seeing oneself as responsible should not be confused with actual responsibility. Our analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…The former group of studies has an entity-level focus and investigates the firm's ethical claims, behaviour, and its relationship with stakeholders (Berrone et al 2007). The latter studies have an internal employee focus (Messikomer and Cirka 2010;Verbos et al 2007;Baker and Roberts 2011). In our study, we investigated social meanings expressed during collective conversations within the SIETAR community and during professional trainings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former group of studies has an entity-level focus and investigates the firm's ethical claims, behaviour, and its relationship with stakeholders (Berrone et al 2007). The latter studies have an internal employee focus (Messikomer and Cirka 2010;Verbos et al 2007;Baker and Roberts 2011). In our study, we investigated social meanings expressed during collective conversations within the SIETAR community and during professional trainings.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies centre on revealed ethics (e.g. Haniffa and Hudaib 2007); others chose to investigate both revealed and applied ethics and their link with, for example, firms' performance (Berrone et al 2007;Baker and Roberts 2011).…”
Section: Living Code Of Ethics and Ethical Identitymentioning
confidence: 99%
“…The search for ethical or moral leadership continues to receive considerable attention in the leadership literature (e.g., Baker and Roberts 2011;Eisenbeiß and Brodbeck 2014;Lawton and Páez 2014;Levine and Boaks 2014). Empirical research on ethical leadership, however, is scarce (Demirtas 2015), and the questions of whether and how the ethics of leadership play out in practice present an important research problem.…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches, they infer, sustain a pre-occupation with the self that supports the pursuit of individual wealth and status, while undermining moral considerations in relation to others. Moreover, de Gama et al (2012) highlight the need for more research on contexts and specific situations where leaders are ''being for the Other'' (p. 105) rather than seeing the Other as an object to do things on and where leaders are practicing responsibility to the Other (Baker and Roberts 2011). Our interest lies in advancing these discussions on the ethics of leadership.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation